The Meaning of Work During the Transition From Vocational Education and Training to Employment - Masdonati, Jonas; Fournier, Geneviève; Lahrizi, Imane Z. (Canadian Journal of Counselling and Psychotherapy, 2022)
We investigated the meaning of work of young adults transitioning from vocational education and training to employment. Meaning of work was operationalized as the combination of work centrality and purposes. Sixty-four young adults were interviewed at the end of vocational education and training and after their integration into the labor market. Qualitative analyses indicated that the centrality of work ranged from high to low and that their work purposes were of five types: earning money, growing, structuring life, contributing to society, and socializing. Quantitative analyses showed that the meaning of work globally did not change through the transition process, and work had a higher relative centrality for men than for women. These results stress the importance of considering the variety of functions and degrees of importance young adults confer to work when entering the labor market as well as integrating the concept of work meaning within counseling research and interventions.